2014
DOI: 10.2478/bpasts-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of pneumatic melt drawing of polypropylene super-thin fibers in the Laval nozzle

Abstract: Abstract. Melt spinning of the fibers by supersonic air jet in the Laval nozzle is a novel, efficient and energy saving method of formation of super-thin fibers. In the process, polymer melt is extruded from a row of orifices and fast drawn by the pneumatic forces. In the modelling, air velocity, temperature and pressure distributions are computed from the k-ω aerodynamic model. Computations of the polymer air-drawing dynamics are based on the mathematical model of melt spinning in a single-, thin-filament app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Figure 2 provides an overview of current major nanofiber production technologies and the fiber diameters that have typically been achieved using those methods. Only the most common processes are mentioned and there are many variants of these methods that we do not discuss in detail [4250].
Fig.
…”
Section: Current Manufacturing Processes For Sub-microfibers and Nanomentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 provides an overview of current major nanofiber production technologies and the fiber diameters that have typically been achieved using those methods. Only the most common processes are mentioned and there are many variants of these methods that we do not discuss in detail [4250].
Fig.
…”
Section: Current Manufacturing Processes For Sub-microfibers and Nanomentioning
confidence: 99%
“…
Fig. 2Nanofiber production technologies and the corresponding fiber diameter range: melt blowing [4], nanoval [42, 43], Laval [42], centrifugal spinning [44], electroblowing [45], drawing [46], island-in-the-sea [47], electrospinning [4], solution electrospinning [4], melt electrospinning [4], self-assembly [48, 49], template synthesis [50]
…”
Section: Current Manufacturing Processes For Sub-microfibers and Nanomentioning
confidence: 99%
“…Laval nozzles are important tools in other fields such as powder metallurgy, including gas-assisted atomization (Allimant et al, 2009 andSi et al, 2014), narrow size nanoparticle synthesis (Li et al, 2008 andJung et al, 2008), or inertial separation of particles (Kanaoka et al, 2001). These type of nozzles can be found as well as part of apparatuses developed for studies concerning spray deposition (Jen et al, 2006), formation of super thin fibers (Blim et al, 2014), hydrogen production (Du et al, 2012), laser cutting (Man et al, 1999), homogeneous or binary nucleation (Kim et al, 2004 andTanimura et al, 2010), infrared (Tanimura et al, 1996 andBenidar et al, 2000) or microwave spectroscopy (Oldham et al, 2014), or hypersonic astrophysical jets simulations (Tordella et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al 19 found that applying air constrictors around the primary air jets could keep the maximum air velocity and temperature in a longer distance. Tan et al 20 and Blim et al 21 studied the characteristic of the Laval-die melt-blown air flow by CFD simulation. In addition, melt-blown dies with louvers were designed, 22 and the spinning experiment verified the better effect of fiber attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al . and Blim et al studied the characteristic of the Laval-die melt-blown air flow by CFD simulation. In addition, melt-blown dies with louvers were designed, and the spinning experiment verified the better effect of fiber attenuation …”
Section: Introductionmentioning
confidence: 99%